Strategies to select soybean segregating populations with the goal of improving agronomic traits - Silva, Fabiana Mota da [UNESP]; Pereira, Elise de Matos [UNESP]; Pedroso Val, Bruno Henrique [UNESP]; Perecin, Dilermando [UNESP]; Di Mauro, Antonio Orlando [UNESP]; Uneda-Trevisoli, Sandra Helena [UNESP] (Univ Estadual Maringa, Pro-reitoria Pesquisa Pos-graduacao, 2018)
The success of breeding programs depends on selection procedures and on the breeding methods adopted for selecting segregating populations. The objective of this study was to evaluate the efficiency of the Bulk method with selection in the F-3 generation (BulkF3) compared to that of Bulk method as well as determine the most effective selection strategy in terms of genetic gain. Twenty segregating populations were selected by two methods. The 60 best families of each method were selected according to their average agronomic performance. An augmented block design was used. The following agronomic traits were evaluated: insertion height of first pod, plant height at maturity, number of branches and of pods per plant, 100-seed weight, and grain yield. For comparison of the methods, genetic component estimates, genetic gain and predicted breeding values were calculated using mixed models (REML and BLUP). The results showed the families obtained with the BulkF3 method were more productive, showed suitable plant height, a larger number of branches and pods, and higher 100-seed weight. The BulkF3 method was found to be an effective selection strategy for soybean improvement.
Keywords: genetic gain; Glycine max; breeding methods; mixed model